2016
DOI: 10.3389/fnbeh.2016.00038
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Modulation of Vocal Behavior in Mouse: Newly Identified 12 kHz “Mid-Frequency” Vocalization Emitted during Restraint

Abstract: While several studies have investigated mouse ultrasonic vocalizations (USVs) emitted by isolated pups or by males in mating contexts, studies of behavioral contexts other than mating and vocalization categories other than USVs have been limited. By improving our understanding of the vocalizations emitted by mice across behavioral contexts, we will better understand the natural vocal behavior of mice and better interpret vocalizations from mouse models of disease. Hypothesizing that mouse vocal behavior would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 61 publications
(110 reference statements)
6
85
2
Order By: Relevance
“…In contrast, calls with the lowest frequency of near 70 kHz are not closely associated with mounting [41]. There is also a recently discovered ‘mid-frequency’ call of mice with a fundamental frequency of around 12 kHz that has been associated with distress [58]. The difference between our 50-kHz and 70-kHz categories therefore does not simply represent a limitation on our measurement, but a functional distinction.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, calls with the lowest frequency of near 70 kHz are not closely associated with mounting [41]. There is also a recently discovered ‘mid-frequency’ call of mice with a fundamental frequency of around 12 kHz that has been associated with distress [58]. The difference between our 50-kHz and 70-kHz categories therefore does not simply represent a limitation on our measurement, but a functional distinction.…”
Section: Discussionmentioning
confidence: 94%
“…Mice were previously shown to change their vocalization pattern in different contexts (Chabout et al, 2012, 2015; Yang et al, 2013; Mun et al, 2015; Srivastava et al, 2015; Gaub et al, 2016; Grimsley et al, 2016; Heckman et al, 2016; Hoier et al, 2016; Seagraves et al, 2016). We therefore hypothesized that head-fixation likely modulates USVs in comparison to non-restrained sessions.…”
Section: Resultsmentioning
confidence: 99%
“…This sets a success rate of at least 60% if all mice undergo the habituation protocol. A few studies have indicated that mice and rats can produce head-restrained sonic and ultrasonic spontaneous vocalizations, however this is the first systematic demonstration of head-restrained social interaction related vocalizations in mammals (Reed et al, 2013; Grimsley et al, 2016). Because not all mice vocalized, we tested several strategies to increase the probability of head-fixed vocalizations but none of these manipulations seemed to be effective.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations